158k views
4 votes
How would you solve the following quadratic equation using the square root property (x-2)^2=4.

1 Answer

1 vote

We have


\begin{gathered} (x-2)^2=4\rightarrow \\ (x-2)^2-4=0 \\ (x-2+2)(x-2-2)=0 \\ (x)(x-4)=0\rightarrow \\ x=0\lor x=4 \end{gathered}

Using the square root property is:


\begin{gathered} x-2=2\lor x-2=-2 \\ x=2+2\lor x=-2+2 \\ x=4\lor x=0 \end{gathered}

User Ilbets
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.